Face to face with orchestra and chorus : a handbook for choral conductors - Moses, Don V., 1936- (Indiana University Press, 2004)
This is a crucial guide for choral conductors who are presented with the daunting task of conducting a full-size orchestra. It provides a survival kit for both novice and experienced choral conductors, with an overview of orchestral instruments and their particular needs, tips for rehearsing an orchestra effectively, and guidelines for proper baton technique. Conductors are walked through six case studies from the Baroque and Classical periods.